FEN BİLGİSİ ÖĞRETMEN ADAYLARININ FARK ETME BECERİLERİNİN İNCELENMESİ. - İNALTUN, Hüseyin (Mehmet Akif Ersoy University Journal of Education Faculty)
Science teachers must attentively engage with students' perspectives, uncover underlying reasons, and shape instructional strategies in a dynamic classroom setting. These practices, which are called noticing skills, play a crucial role in students' science learning. Hence, examining the current level of noticing skills of pre-service science teachers is necessary to provide effective support for their development. Therefore, this study employed a basic qualitative research design to investigate the noticing skills of 11 fourth-year pre-service science teachers enrolled in a state university in Turkey. The data collected from pre-service teachers, including their lesson plans, student artifacts generated during their internships, and responses to open-ended questions, were analyzed using content analysis techniques. The results showed that pre-service teachers generally obtained the artifacts they thought reflected the students' understanding of the relevant science subject through activities that required students to remember what was explained in the lesson. Moreover, the results revealed that preservice teachers tended to attend to the accuracy of student artifacts rather than the students' scientific reasoning and thought. Finally, the results showed that pre-service teachers analyzed student artifacts from a superficial perspective of whether the content was learned, without attempting to uncover the underlying reasoning behind the student artifacts.